Cellular Fucosylation Inhibitors Based on Fluorinated Fucose‐1‐phosphates. Issue 12 (2nd February 2021) - Pijnenborg, Johan F. A.; Visser, Eline A.; Noga, Marek; Rossing, Emiel; Veizaj, Raisa; Lefeber, Dirk J.; Büll, Christian; Boltje, Thomas J.
Abstract: Fucosylation of glycans impacts a myriad of physiological and pathological processes. Inhibition of fucose expression emerges as a potential therapeutic avenue for example in cancer, inflammation, and infection. In this study, we found that protected 2‐fluorofucose 1‐phosphate efficiently inhibits cellular fucosylation with a four to seven times higher potency than known inhibitor 2FF, independently of the anomeric stereochemistry. Nucleotide sugar analysis revealed that both the α‐ and β‐GDP‐2FF anomers are formed inside the cell. In conclusion, we developed A2FF1P and B2FF1P as potent new tools for studying the role of fucosylation in health and disease and they are potential therapeutic candidates. Abstract : Fucosylation of glycans impacts a myriad of physiological of pathological activities. In this study, new fucosylation inhibitors based on fluorination of fucose‐1‐phosphates were developed. Inhibitors A2FF1P and B2FF1P are potent, specific, non‐toxic, inhibit fucosylation for multiple days and have a known mechanism of action. These new tools will help study the role of fucosylation in health and disease and are potential therapeutic candidates.